The White House a pop-up of our nation's home - Gilder, Richard Watson 1844-1909 (Orchard Books, 2016)
"In this spectacular pop-up guide to the White House by bestselling paper engineer Robert Sabuda, readers can take a tour behind the scenes of the office of the executive branch and the residence of the president and his family. Travel through time as you open each spread and discover the North Face of the White House, the East Room, the Lincoln Bedroom, the Rose Garden, the Oval Office, and the South Lawn of the White House. The text includes the poem "Inauguration Day" by Richard Watson Gilder, adapted by Robert Sabuda. Every American president since John Adams has lived in the White House. More than 1.5 million people visit the White House every year. According to First Lady Michelle Obama, "It's the 'People's House.' It's a place that is steeped in history, but it's also a place where everyone should feel welcome." The White House: A Pop-Up of Our Nation's Home is perfect for Presidents Day and the upcoming election"...